The use of ULVA as a feed supplement in the development of an artificial diet and feeding regimes to produce export quality roe from the sea urchin Tripneustes gratilla (Linnaeus) - Cyrus, Mark Digby (Department of Biological Sciences, 2014)
Includes bibliographical references.